MARKETING POLITIK CALON TUNGGAL PADA PILKADA KABUPATEN TANGERANG TAHUN 2018 - Noer Apptika Fujilestari (Lensa, 2023)
The phenomenon of a single candidate pair in the 2018 Pilkada is not the first to have occurred since the Pilkada were held directly. This becomes an interesting political dynamic, indicating that democracy does not work according to its spirit. Political parties have strong control over the emergence of a single candidate, political parties should be able to carry out political regeneration and political education to the public for the sake of democracy. The implementation of the 2018 Tangerang Regency regional elections was in the public spotlight with the presence of Ahmed Zaki Iskandar and Mad Romli as the sole candidate pair. Even though the political capital owned by this single pair is quite strong and victory can be ensured without holding elections, procedurally the implementation of regional election political campaigns must still be carried out to convince constituents of this single candidate. In carrying out political campaigns, it is very important to carry out political marketing so that the campaign strategies and materials delivered are right on target. This study uses a qualitative descriptive method to explore and analyze existing political phenomena. The results of this study show that political marketing carried out by this single candidate pair runs optimally by running four indicators of political marketing, namely; Product, Place, Price and Promotion. Of the four indicators, the political marketing of this single candidate is strongest in the product indicator where this single candidate who is also an incumbent has more access than the other prospective regents/deputy regents. The character built by Ahmed Zaki Iskandar succeeded in convincing constituents to re-elect him.